A Lesser Known Underutilized Sword bean[Canavalia gladiata (Jacq.) DC.] : Cultivationand Conservation in Bihar and Jharkhand - Chourasia, H K; Pan, T K (Indian Horticulture, 2025)
There are several underutilized plant species available in nature. Many cultivated vegetable plant species, which originated in the wild, constitute an important part of the daily diet of both rich and poor people. Canavalia gladiata (Jacq.) DC., commonly known as Sword bean, belongs to the family Fabaceae. This species was collected from Kanihmoh Tola, Bihar, and Chihutia, Mohanpur, Jharkhand. Sword bean has been known for its traditional medicinal properties and is used to treat a number of diseases, such as cancer, sinus infections, and supportive conditions. It also possesses hypertension-relieving, antioxidant, and antibacterial effects. Despite its therapeutic potential, this plant can also be exploited for vegetable use. The present report is an effort by the authors to raise awareness about the conservation, cultivation, and health benefits of the Sword bean.